(untitled) (Development Service Industry Management, 2024)
The article examines the problem of complementarity of the concepts of project management and process management in modern management theory. The authors summarized the differences in the nature of processes and projects in the organization. On the basis of existing approaches in the theory of project management and existing management practices, the authors have developed a systematization of processes implemented in project management. The existing differences between project and process management are determined. The authors concluded that both presented concepts are intended to strengthen the competitiveness and improve the company’s performance. Processes at the enterprise naturally coexist and interact with projects, they complement each other - a dual approach (processes-projects). This involves cooperation, coexistence and complementarity of enterprise management elements, in particular: processes, projects and knowledge. Therefore, for effective management of an organization (enterprise, institution) it is not enough just to co-exist processes and projects (concepts of their management) - their cooperation is necessary, which is also manifested in the transfer of knowledge within the organization. Therefore, in organizations, it is necessary to determine the relationship between the elements of "processes - projects". These categories should be considered in terms of consistency and synergy, in the context of the products and services provided by the organization, and the satisfaction of customer needs and expectations.